Contribuição para o processo de aperfeiçoamento da informação para a decisão e avaliação do desempenho patrimonial, econômico e financeiro dos centros de tradições gaúchas do estado de São Paulo - Fighera, Francisco Carlos (2005)
The object of this research is to study the accounting and management information systems currently existing in the Centros de Tradições Gaúchas (CTG s) (Centers of Gaúcho Traditions) in the State of São Paulo and their utilization as a management assistance tool. One proposes also to see if the accounting systems attend to the Fundamental Principles of Accounting and Brazilian Accounting Norms. The interest in the choice of the theme chosen for this work is justified among others, by the necessity of helping these entities to improve their management system, through organized and structured accounting, financial, management and results demonstrations. The starting point was based on the supposition that Accounting can be an important contribution, by making available accounting and financial information to the entities denominated (CTGs) in the State of São Paulo, which would be useful and utilized in helping the decision making process. In order to reach the proposed objective, field research was carried out in seven of the sixteen CTGs currently existing in the State of São Paulo, utilizing a procedure of intentional sampling, where administrative and accounting data was collected, through a questionnaire The research was aimed at finding out which accounting and financial reports were given the most importance by the management of the CTGs and how they utilized them to evaluate the performance of their actions as heads of these organizations. The incipient use of accounting information was noted, especially in the financial demonstrations elaborated in accordance with the norms established by the Federal Accounting Counsel, where constant emphasis is made to bookkeeping reports. Having made a diagnosis of the entities which were studied, a number of programmed, structured and related accounting, financial and management reports were suggested, which will enable the managers of the CTGs in the State of São Paulo to show the results of the activities carried out and their patrimonial and financial situation, thus providing a better evolutional analysis of same